Nonconscious activation of placebo and nocebo pain responses - Jensen, Karin B; Kaptchuk, Ted J; Kirsch, Irving; Raicek, Jacqueline; Lindstrom, Kara M; Berna, Chantal; Gollub, Randy L; Ingvar, Martin; Kong, Jian (Proceedings of the National Academy of Sciences - PNAS, 2012)
The dominant theories of human placebo effects rely on a notion that consciously perceptible cues, such as verbal information or distinct stimuli in classical conditioning, provide signals that activate placebo effects. However, growing evidence suggest that behavior can be triggered by stimuli presented outside of conscious awareness. Here, we performed two experiments in which the responses to thermal pain stimuli were assessed. The first experiment assessed whether a conditioning paradigm, using clearly visible cues for high and low pain, could induce placebo and nocebo responses. The second experiment, in a separate group of subjects, assessed whether conditioned placebo and nocebo responses could be triggered in response to nonconscious (masked) exposures to the same cues. A total of 40 healthy volunteers (24 female, mean age 23 y) were investigated in a laboratory setting. Participants rated each pain stimulus on a numeric response scale, ranging from 0 = no pain to 100 = worst imaginable pain. Significant placebo and nocebo effects were found in both experiment 1 (using clearly visible stimuli) and experiment 2 (using nonconscious stimuli), indicating that the mechanisms responsible for placebo and nocebo effects can operate without conscious awareness of the triggering cues. This is a unique experimental verification of the influence of nonconscious conditioned stimuli on placebo/nocebo effects and the results challenge the exclusive role of awareness and conscious cognitions in placebo responses.